Influência da ozonização na desidratação de lodo de estação de tratamento de água - Ferrari, Keila Fernanda Hedlund (2020)
To treat water aiming human consumption various unit operations are required at the Water Treatment Plants (WTPs), however, the potabilization of water leads to high waste generation. Disposal of sludge in water bodies causes a lot of damage to the environment, so waste WTPs must be treated and disposed of properly. Sludge treatment aims at reducing moisture and proper disposal of solid material. Dehydration increases solids concentration, reducing sludge volume. In sludge treatment ozonation can positively influence dehydration. Ozone (O3) is an oxidizer capable of degrading several compounds, as well as releasing water from the sludge particle. However, there are no studies in the literature on the use of ozone for the treatment of WTP sludge. Thus, this study aimed to evaluate the influence of ozonation on the characteristics of thickened sludge and clarified water, as well as to investigate the effect of ozonation on the sludge dewatering WTP of São Gabriel/RS (Southern Brazil). The experimental investigation was divided into four stages: Preliminary tests, determining the effects of ozonation and thickening of sludge; Dehydration Evaluation, identifying the influence of pre-ozonation and flocculation for sludge dewatering; Evaluation of clarified water and thickened sludge after pre-ozonation and flocculation; Geotextile dehydration, determining the influence of ozonation and flocculation on sludge drainage and dehydration. The results of the first stage showed that the sedimentation time changed only the total solids (TS) and fixed total solids (TFS) content, while O3 had an effect on all evaluated parameters. Treatment with higher ozone dosage (1.1 gO3/gST) resulted in higher concentrations of TS (39.15 g/L), TFS (28.90 g/L), total carbon removal (13% C) and aluminum solubilization. (88.56 mg/L Al), and lower particle size (42.6 µm PS) and pH (3.6). The combination of ozonation and flocculation treatment presented lower specific resistance to filtration (SRF) for sludge, with results between 3.19 - 5.85E+12 m/kg. The optimized ozone and polymer dosing results were 0.24 gO3/gST and 4 mg pol/gST. After pre-ozonation and flocculation in dosages applied to clarified water showed lower turbidity, color, pH, aluminum, iron and lead, but higher conductivity, anion concentration (fluoride, chloride, nitrate and sulfate), manganese and barium. The sludge obtained higher concentration of TS (22.14±1.14 g/L) and PS (42.63±1.48µm), and lower sludge volumetric index (IVS) (22.6±0.65 mL/g), with negative zeta potential (ZP). The use of geotextile for ozonation and flocculation sludge obtained the best drainage and dehydration, with higher accumulated drainage volume (4519.5 mL) and lower turbidity (12 NTU) at the end of the drainage time (90 minutes). Higher TS content (10.94±0.93%), lower moisture (9.02±0.67% M) and C content (6.90±0.18%), with dehydration efficiency (DE) of 89.9%. The influence of ozonation on sludge dehydration has been shown to be efficient with a significant improvement in WTP sludge dehydration under study.